1984
DOI: 10.1007/bf00572770
|View full text |Cite
|
Sign up to set email alerts
|

Methods for evaluating the taste of paediatric formulations in children: A comparison between the facial hedonic method and the patients' own spontaneous verbal judgement

Abstract: The aim of the study was to evaluate two essentially different methods of assessing differences in children's taste preferences with regard to five different paediatric penicillin formulations. The study was performed with a parallel group design comparing five groups. A taste evaluation was recorded in 103 children with upper respiratory tract infections after a single therapeutic test dose. First the patient's own spontaneous verbal judgement was recorded then a judgement was arrived at using a hedonic scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 3 publications
1
46
0
Order By: Relevance
“…Other studies with children which reinforce this view include those by Guthrie, Rapoport, and Wardle (2000), who found that 3-to 5-year-old children gave the most reliable data on food preferences when real foods were the stimuli compared to plastic models of the foods or photographs, Kroll (1990), who found that a child-oriented verbal scale was more appropriate than a hedonic or face scale for discrimination of the sweetness of an orange beverage, and James (1996), who reported that ranking was inappropriate with 8-to 9-year-olds for discriminating levels of sweetness, saltiness, sourness, or bitterness in taste mixtures. On the other hand, Leon, Couronne, Marcuz, and Koster (1999) obtained similar satisfactory results using a paired comparison method, ranking by elimination or hedonic categorization to measure children's food preferences, as did Sjovall, Fogh, Huitfeldt, Karlsson, and Nylen (1984) using a hedonic category scale and facial scale.…”
Section: Discussionmentioning
confidence: 77%
“…Other studies with children which reinforce this view include those by Guthrie, Rapoport, and Wardle (2000), who found that 3-to 5-year-old children gave the most reliable data on food preferences when real foods were the stimuli compared to plastic models of the foods or photographs, Kroll (1990), who found that a child-oriented verbal scale was more appropriate than a hedonic or face scale for discrimination of the sweetness of an orange beverage, and James (1996), who reported that ranking was inappropriate with 8-to 9-year-olds for discriminating levels of sweetness, saltiness, sourness, or bitterness in taste mixtures. On the other hand, Leon, Couronne, Marcuz, and Koster (1999) obtained similar satisfactory results using a paired comparison method, ranking by elimination or hedonic categorization to measure children's food preferences, as did Sjovall, Fogh, Huitfeldt, Karlsson, and Nylen (1984) using a hedonic category scale and facial scale.…”
Section: Discussionmentioning
confidence: 77%
“…Over the next two days, the remaining flavors were tested at the same time of administration, if there was prescription of the formulation. Subjects were also observed by the researcher for spontaneous reactions, through facial or body expressions and comments on likes and dislikes [33][34][35] (Method 2) and data was recorded and classified into Positive, Negative or No reaction, as shown in (Table 1). Easy administration, sucking motions, licking lips, smile, stop crying, opening the mouth asking for more, nod positively, say "good," "I want", "liked", "tasty", "very good "or "better than the last one" .…”
Section: Acceptance Testmentioning
confidence: 99%
“…This scale has been shown to be a reliable method for assessing sensory perceptions in children in this age group. 5 Here, 0 represented the worst taste or odour imaginable and 100 represented the absence of taste or odour. Patients 11 to 18 years old were asked to measure taste, touch, sight, and odour perceptions with a numeric rating scale.…”
Section: Data Collectionmentioning
confidence: 99%